PENGGUNAAN GADGET DAN PENYESUAIAN DIRI SISWA KELAS VIII DI SMP NEGERI 4 PEKANBARU - Winny Asnawi; Elni Yakub; Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Based on preliminary observations conducted on students of SMP Negeri 4 Pekanbaru encountered phenomenon of gadget use among students has reached 90%, this has been troubling parents because many students are busy with gadgets so less time off and lack of communication with people around. The purpose of this study is to determine the use of gadget, and to know the picture of self-adaptation of students. The type of research used in this study is the type of descriptive quantitative research. Based on the results of the research, the use of gadgets in terms of duration of the use of gadgets most often use gadgets more than 10 hours a day, from the aspect of the purpose of use of gadgets most often use gadgets for shopping online, the influence of gadgets on the physical most often experienced by students is back pain due too long to bow. Adjustment in terms of the ability to control the highest emotional highs is able to express a sense of happiness in front of a friend. The aspect of overcoming the psychological mechanism is to tell the truth. Aspects are able to overcome frustration, avoid saying harshly. Rational and self-directed consideration is to ask a friend when he finds a difficult problem. The aspect of having the highest learning ability is to collect tasks on time. The aspect of making use of the experience of the past of the highest is preparing future plans and on the aspect of being objective and realistic the highest is being able to overcome limitations.Keywords: Gadget Use, Self-Adjustment